2018
DOI: 10.3390/insects9020046
|View full text |Cite
|
Sign up to set email alerts
|

Entomofauna Associated with Agroforestry Systems of Timber Species and Cacao in the Southern Region of the Maracaibo Lake Basin (Mérida, Venezuela)

Abstract: Agroforestry systems are environment-friendly production systems which help to preserve biodiversity while providing people with a way of earning a living. Cacao is a historically important crop in Venezuela that traditionally has been produced in agroforestry systems. However, few studies have evaluated how different trees used in those systems affect the dynamics and abundance of insects. The present study evaluated the entomofauna assemblages associated with different combinations of four timber-yielding tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 65 publications
1
2
0
Order By: Relevance
“…Formicidae was the most abundant Hymenoptera family in both systems. For this family abundance, richness and diversity were significantly higher in the silvopasture, as has been found previously 15,[66][67][68] . In the silvopastoral system this increase in ant diversity could be due to the differences in tree physiology and structural complexity, resulting in an increase in diversity 69,70 .…”
Section: Discussionsupporting
confidence: 86%
“…Formicidae was the most abundant Hymenoptera family in both systems. For this family abundance, richness and diversity were significantly higher in the silvopasture, as has been found previously 15,[66][67][68] . In the silvopastoral system this increase in ant diversity could be due to the differences in tree physiology and structural complexity, resulting in an increase in diversity 69,70 .…”
Section: Discussionsupporting
confidence: 86%
“…In cacao agroecosystems from Merida (Venezuela), Mazón (2015) and Mazón et al (2018) reported 33 and 23 families of parasitoid wasps, respectively. Again, the richest families were similar to what we obtained in this study: Braconidae, Ichneumonidae, Scelionidae, Pteromalidae, Figitidae, Encyrtidae, and Mymaridae.…”
Section: Parasitoid Wasps In Cacao Agroecosystemsmentioning
confidence: 99%
“…In addition to vegetation, ecological restoration implies the recovery of the entire set of attributes of the original ecosystem (Amazonas et al 2018), such as the entomofauna community. However, little is known about insect dynamics in early areas of AFS, which has remained relatively understudied (Bos et al 2007;Dantas et al 2012;Mazón et al 2018;Aquino et al 2020;Paiva et al 2020). We hypothesized that different restoration techniques and types of weed control change the composition of edaphic entomofauna.…”
mentioning
confidence: 96%